The Transformation of the Meiji Period in Japan in the Light of the Textbook Historical Narrative in Elementary School - Marciniak, Dominika (Sensus Historiae, 2025)
The subject of this article is the historical narrative concerning the history of Japan, with particular emphasis on the changes taking place in the discussed country during the Meiji period. This subject was included in three series of textbooks for teaching and learning history in primary schools. Drawing on postcolonial studies, in my research I addressed the issue of the place of the history of Japan in the school history curriculum in Poland. The analysis begins with a historiographical examination of the history of Japan during the Meiji reforms. Then, taking into account the phenomenon of didactic transposition, I looked at how the findings of historians on the Meiji era were used in the school textbook narrative. This procedure was aimed at answering from what perspective the history of Japan is presented in school history.